Botanic Gardens and Their Role in Plant Biodiversity Conservation - Haryanto . (Media Konservasi, 1992)
William Conway (1998) once wrote: "In the preservation of biological diversity (biodiversity), the use of technology is a last resort. When the preservation of ecosystemsfaltery, their fragments may have to be cared for piece by piece". However, further he said that intensive care and biotechnology can preseve some diversity thet would otherwisw be lost. But thegreates dimension of such preservation is depressingly slight compared with that which can be or could have been sustained in adequately designed and protected nature reserves and by understanding accomodation outside preserved areas.